International Macroeconomic Policy Coordination When Policymakers Do Not Agree on the True Model: Reply - Frankel, Jeffrey A.; Erwin, Scott; Rockett, Katharine (American Economic Review, 1992)
In their paper in this Review, Jeffrey A. Frankel and Katherine E. Rockett (1988) show that when international macroeconomic policymakers do not agree on the correct macroeconomic model, they will still be able to agree on a cooperative policy package that each believes will improve his welfare. Yet the package may turn out to move target variables in the wrong direction. From extensive simulation experiments with ten empirical models, Frankel and Rockett conclude: ...the bargaining solution is as likely to reduce welfare as to improve it. But more definitions of cooperation should be investigated... (p. 338). In this paper we propose an alternative definition of a policy bargain to that investigated by Frankel and Rockett and show that results in a higher success rate and higher expected utility in cooperation exper-iments. It follows from our finding that, given uncertainty or ignorance about the true model, a measure of disagreement is beneficial because facilitates a simple robustness check for proposed policy bargains. As Frankel and Rockett (1988 p. 328) acknowledge: it is the countries' failure to perceive the true model, not their failure to agree with each other per se, that alters the standard conclusion regarding coordination (i.e., is uncertainty, not disagreement, that leads to failure). We go further: given the inevitable failure to perceive the true model, some disagreement is better than unanimity in error. Extreme disagreement about the nature of reality, however, makes robust bargains impossible.